Who writes for black children? : African American children's literature before 1900 - Capshaw, Katharine; Duane, Anna Mae, 1968- (University of Minnesota Press, 2017)
"Until recently, scholars believed that African American children's literature did not exist before 1900. Now, Who Writes for Black Children? opens the door to a rich archive of largely overlooked literature read by black children. This volume's combination of analytic essays, bibliographic materials, and primary texts offers alternative histories for early African American literary studies and children's literature studies. From poetry written by a slave for a plantation school to joyful "death biographies" of African Americans in the antebellum North to literature penned by African American children themselves, Who Writes for Black Children? presents compelling new definitions of both African American literature and children's literature. Editors Katharine Capshaw and Anna Mae Duane bring together a rich collection of essays that argue for children as an integral part of the nineteenth-century black community and offer alternative ways to look at the relationship between children and adults. Including two bibliographic essays that provide a list of texts for future research as well as an extensive selection of hard-to-find primary texts, Who Writes for Black Children? broadens our ideas of authorship, originality, identity, and political formations. In the process, the volume adds new texts to the canon of African American literature while providing a fresh perspective on our desire for the literary origin stories that create canons in the first place. Contributors: Karen Chandler, U of Louisville; Martha J. Cutter, U of Connecticut; LuElla D'Amico, Whitworth U; Brigitte Fielder, U of Wisconsin-Madison; Eric Gardner, Saginaw Valley State U; Mary Niall Mitchell, U of New Orleans; Angela Sorby, Marquette U; Ivy Linton Stabell, Iona College; Valentina K. Tikoff, DePaul U; Laura Wasowicz; Courtney Weikle-Mills, U of Pittsburgh; Nazera Sadiq Wright, U of Kentucky"--